(untitled) (Cadernos de Ética e Filosofia Política, 2019)
The present paper attempts to clarify the Kantian concept of maxim. Its object is to provide an interpretation that places the assignment of different functions to this concept in the Kantian philosophy. The author explores also the consequences of his analysis for the solution of the antinomy of teleological judgment in the third Critique. At the heart of this antinomy is Kant's contention that all "semblance" (Anschein) on a conflict between the mechanistic and teleological maxims stems from the confusion of a principle of reflective with one of determinative judgment.